2020
DOI: 10.1002/ehf2.12591
|View full text |Cite
|
Sign up to set email alerts
|

Serum retinol‐binding protein 4 as a predictor of cardiovascular events in elderly patients with chronic heart failure

Abstract: Aims RBP4 is an adipokine with adverse effects on cardiovascular system. Increased circulating retinol-binding protein 4 (RBP4) has been linked to chronic heart failure (CHF). However, whether elevated RBP4 is correlated with a poor prognosis in elderly patients with CHF remains unclear. The aim of this study was to evaluate the prognostic value of serum RBP4 in elderly patients with CHF. Methods and results We enrolled 934 consecutive elderly patients (aged 60 years and older) with CHF and 138 age-matched and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Additionally, RBP4 levels are related to large VLDL and small-dense LDL subfractions in subjects with and without diabetes [32]; mean LDL size in morbid obese patients was noticed as well [33]. However, other studies did not confirm these results [34,35]. In this study, we did not observe correlations between RBP4 and total cholesterol, triglyceride, LDL-C levels, and mean LDL size, but there was a positive correlation between RBP4 and VLDL subfraction levels in obese and lean non-diabetic subjects.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, RBP4 levels are related to large VLDL and small-dense LDL subfractions in subjects with and without diabetes [32]; mean LDL size in morbid obese patients was noticed as well [33]. However, other studies did not confirm these results [34,35]. In this study, we did not observe correlations between RBP4 and total cholesterol, triglyceride, LDL-C levels, and mean LDL size, but there was a positive correlation between RBP4 and VLDL subfraction levels in obese and lean non-diabetic subjects.…”
Section: Discussionmentioning
confidence: 95%
“…At the same time, elevated serum RBP-4 was associated with metabolic syndrome components [ 41 ]. Previous research found a significant positive correlation between RBP-4 levels and CAD severity [ 23 , 42 , 43 , 44 ]. All of these studies support the present study’s outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…10). Moreover, cardiomyocytes are not a homogenous group of cells as can be seen in bulk and single cell RNA-seq, this is also true on the protein level where a small subset of proteins show variability between cardiomyocytes in a mosaic pattern and can likely be further altered under pathological conditions 96,97,123 .…”
Section: Discussionmentioning
confidence: 99%
“…Reverse was true for some of the genes that are reported to be involved in heart failure Kininogen 1 (KNG1) 94,95 , Retinol Binding Protein 4 (RBP4) 96 , Apolipoprotein B (APOB) 97 (Supplementary Table 7&8; Supplementary Fig. 10).…”
Section: Human Left Ventricular Tissue Proteome Analysis Highlighted mentioning
confidence: 99%